TELEVISION & INTERNET AS CHANNELS OF SHAPING PUBLIC PОLITICAL CONSCIOUSNESS - V. P. Cherkasova (Vestnik MGIMO-Universiteta)
The author examines specific characteristics and prospects for the development of TV and the Internet as two major channels of media-manipulation. The emphasis is put on the impact of these channels of information on public political consciousness. Television and internet seem to be antagonistic. Internet is based on iterative communication and feedback, and allows both producing and receiving information. Television is a one way channel of communication and it doesn’t support feedback, it allows only receiving information. The author believes that internet is gaining significant influence and it’s going to transform in the future due to the evolution of the means of control of the citizens behavior and attitudes by governments as well as new possibilities it offers to citizens to oppose information manipulations of authorities. Still, internet is not universally available, which deteriorates its potential as an instrument of political influence. In the foreseeable future the television will remain the most important means of communication and will significantly shape the political preferences of citizens, although its’ role will gradually decrease. At present internet hasn’t replaced television in Russia as high speed internet is not available for every family in Russia.